The dynamics of biofilm overgrowth of Enterococcus faecalis - Synetar, E. A.; Brych, O. I. (Regulatory Mechanisms in Biosystems, 2015)
The nature of microorganisms can exist in two physiological forms that allow microbes to preserve livelihoods and continue their life cycle. The first is the population of planktonic forms of microorganisms which live freely in the environment with the developed systems of active and passive mobility, contributing to the rapid spread of a liquid medium. The second forms are those expressing specific mechanisms of adhesion, and able to aggregate on biogenic and abiogenic surfaces. Even in the deep sea vast number of species of bacteria live in their inherent horizons. Thus, the study of biofilms tube life support systems, diagnostic, laparoscopic devices during prolonged catheterization of the urinary system is of great practical, theoretical and biological significance in medicine and biology. For almost 20% of catheter-associated infections antibiotic therapy is uneffective, particularly through the formation of microbial biofilms on the surface of urinary catheters. We characterized the dynamics of biofilm growth of Enterococcus faecalis on fragments ofsilicone catheter. The study was conducted using bacteriological and electron microscopic techniques. Study of the dynamics of biofilm formation was performed using E. faecalis strain 49, which is isolated from the urine of persons who are not the patients of the urological department of resuscitation and intensive therapy. Using scanning electron microscopy we have established dynamics and phase attachment ofE. faecalis bacteria and subsequent overgrowth of silicone catheter surface. Aftercalculations, index of adhesion on the turbulent wall amounted to 0,49 microbial cells. That is, every other cell of the monolayer adhered on the catheter. Area of biofilm growth of E. faecalis after 24 hour incubation was equal to 51.5 μm2, in 48 hours it increased to 231.5 μm2. After 72 hours of incubation we recorded the increase in biofilm growth of E. faecalisto 1922,8 μm2. The results were obtained on fragments of catheters, immersed in broth in vertical position. This orientation has excluded the deposition of germs by sedimentation, i.e. by gravity. It is known that after the logarithmic phase and achieving M-concentration for a few hours microbes starttodie and their possible deposition mayoccur. Therefore, our results confirm the formation of biofilm, instead of sedimentation of dead microbes. Our study shows that biofilm is “the way of overgrowth on artificial and natural surfaces by microorganisms that are kept on them by exopolymer membranes”.